Expression of immune, antioxidant and stress related genes in different organs of common carp exposed to indoxacarb - Melika Ghelichpour (2019)
© 2019 Elsevier B.V. The aim of the present study was to investigate the effects of chronic exposure of common carp (Cyprinus carpio) to indoxacarb on immune, antioxidant and stress gene expression. After 21 days exposure to 0, 0.75, 1.5 and 3 ppm indoxacarb, expression of IL-1β, IL-8, IL-10, TNF-α, IFN-γ, SOD, CAT, HSP70, IGF-I and IGF-II were assessed in liver, kidney and gills. In general, exposure to low concentration of indoxacarb increased inflammatory cytokine gene expression (IL-1β, IL-8, IL-10, TNF-α and IFN-γ) and inhibits inflammatory cytokines’ expression at higher concentrations. The assessment of antioxidant gene expression (SOD and CAT) in different organs indicate that they were increased by low concentrations of indoxacarb to deal with primary oxidative situation. However, higher concentrations of indoxacarb caused reduction in oxidative gene expression. IGF genes expression in liver significantly increased at a concentration of 0.75 ppm treatment, then it decreased at 1.5 ppm indoxacarb and increased again by increasing in the indoxacarb concentration to 3 ppm. The expression of HSP70 in kidney showed a significant elevation in 0.75 and 1.5 ppm treatments compared with 3 ppm treatment and the control group. The expression of this gene in liver was significantly increased in 1.5 and 3 ppm treatments. The same pattern of expression was also observed in gill. Overall, indoxacarb exposure affects common carp health at transcription levels. Changes in the genes expression generally suggest that indoxacarb exposure led to interference in inflammation, oxidative stress and tissue damage.